The Rudd Government Australian Commonwealth Administration 2007-2010 - Aulich, Chris (ANU Press, 2010)
This edited collection examines Commonwealth administration under the leadership Prime Minister Kevin Rudd from 2007-2010. This was a remarkable period in Australian history: Rudd's government was elected in 2007 with an ambitious program for change. However, as the chapters in this book demonstrate, these ambitions were thwarted by a range of factors, not the least being Rudd's failure to press ahead when he confronted 'road blocks' such the ETS or managing his massive agenda which constantly elevated issues to 'first order priority'. Although he started his term with stratospheric approval ratings, only two years later his support had collapsed and on 24 July 2010 he became the first sitting Prime Minister to be removed by his own Party before the expiry of his first term. In this book, expert contributors consider the Rudd Government's policy, institutional and political legacy. The 14 chapters are organized into four sections, outlining the issues and agendas that guided Rudd's government, changes to the institutions of state such as the public service and parliament, followed by discussions of key issues and policies that marked Rudd's term in office. The final section examines Rudd's leadership and reflects on the personal foibles and political factors that brought his Prime Ministership undone. The Rudd Government has been produced by the ANZSOG Institute for Governance at the University of Canberra. It is the tenth in a series of books on successive Commonwealth administrations. Each volume has provided a chronicle and commentary of major events, policies and issues that have dominated successive administrations since 1983. As with previous volumes in the series, contributors have been drawn from a range of universities and other organisations.